2015
DOI: 10.1007/s00374-015-1069-1
|View full text |Cite
|
Sign up to set email alerts
|

Grazing modifies inorganic and organic nitrogen uptake by coexisting plant species in alpine grassland

Abstract: To study how grazing affects the uptake of inorganic and organic N forms, three focal plant species (i.e., the graminoid species Kobresia pygmaea, which decreases with grazing, and the forbs Potentilla bifurca and Potentilla multifida, which increase with grazing) were selected in ungrazed and grazed plots in an alpine meadow on the Tibetan Plateau. Three times during the growing season (i.e., June, July, and September), these plots were injected with 15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…We found that the grasslands dominated by sedges (e.g., Heleocharis uniglumis , Carex enervis , and Kobresia humilis ) had a larger decrease in soil pH than the grasslands dominated by grass species (e.g., Leymus chinensis , Stipa grandis , and Stipa purpurea ). This is because the sedge species generally show relatively high absorption rates for NH 4 + (Jiang et al, 2016), which can be replaced by H + , thus decreasing the soil pH (Berthrong et al, 2009). Grazing exclusion also led to significant decreases in the deep soil pH for forb and shrub species (e.g., Artemisia desertorum and Astragalus adsurgens ) in grasslands as a result of the deep roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the grasslands dominated by sedges (e.g., Heleocharis uniglumis , Carex enervis , and Kobresia humilis ) had a larger decrease in soil pH than the grasslands dominated by grass species (e.g., Leymus chinensis , Stipa grandis , and Stipa purpurea ). This is because the sedge species generally show relatively high absorption rates for NH 4 + (Jiang et al, 2016), which can be replaced by H + , thus decreasing the soil pH (Berthrong et al, 2009). Grazing exclusion also led to significant decreases in the deep soil pH for forb and shrub species (e.g., Artemisia desertorum and Astragalus adsurgens ) in grasslands as a result of the deep roots.…”
Section: Discussionmentioning
confidence: 99%
“…show relatively high absorption rates for NH 4 + (Jiang et al, 2016), which can be replaced by H + , thus decreasing the soil pH (Berthrong et al, 2009). Grazing exclusion also led to significant decreases in the deep soil pH for forb and shrub species (e.g., Artemisia desertorum…”
Section: Factors Affecting Soil Phmentioning
confidence: 99%
“…Additionally, the changes in species composition under high grazing intensities can also affect the availability of nutrients. For example, grazing can increase the number of forbs, which can absorb more N than graminoids [6,30]. In addition, unpalatable and grazing-tolerant annual species become dominant under heavy grazing pressure, and those species usually have higher nutrient contents with lower leaf C:N ratios than perennial grass species [6,8,13,30].…”
Section: Effects Of Grazing On Stoichiometric Characteristics Of Plantsmentioning
confidence: 99%
“…However, legume species (including Gueldenstaedtia diversifolia and Medicago ruthenica) have strong nitrogen fixation ability, but weak absorption efficiency for NH 4 + and NO 3 À (Wang et al 2012). The different uptake patterns of different species have been demonstrated by many studies in alpine meadows and other ecosystems (McKane et al 2002;Gao et al 2014;Jiang et al 2015;Li et al 2015). Thus, a decrease in the diversity of the functional groups might enhance the contents of different nitrogen forms in the soil.…”
Section: Effects Of Litter On Plant Diversitymentioning
confidence: 99%